Shari'ah non-compliant events in Islamic banks in the practice of tawarruq financing in Malaysia - Ali, Mohammad Mahbubi (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2017)
Shari'ah is the backbone of the Islamic banks (IBs) in which they operate. Failure to observe Shari'ah compliance therefore triggers negative repercussions in IBs. Over the last two decades, a number of cases have been brought to court to challenge the legitimacy of Islamic banking products. In some cases, these challenges have resulted in financial loss for IBs. In view of this, Bank Negara Malaysia (BNM) has initiated commendable efforts to create a Sharī'ah non-compliant risk culture in IBs. However, ensuring Shari'ah compliance is not a simple and straightforward matter. As IBs continue to witness a remarkable growth and product complexity, Sharī'ah non-compliance incidents and disputes are likely to emerge. This research investigates various forms of potential Sharī'ah non-compliant (SNC) events, and the Sharī'ah methodology adopted to deal with them, in IBs in the practice of tawarruq financing in Malaysia. The research also identifies the SNC event determinants and the various mechanisms for their mitigation. The research employs the Hanafi and the majority of the jurists (jumhËr) approaches in dealing with an invalid contract to examine the treatment of SNC events in tawarruq financing. A self-administered questionnaire was distributed to 16 respondents to explore SNC events in 16 Islamic commercial banks which related to the practice of tawarruq financing in Malaysia. The research also includes a series of structured interviews with practitioners, regulators, Shari'ah advisors and researchers/academicians. Analytic Network Process (ANP) is adopted to prioritise the SNC event determinants as well as measures for their mitigation. The research found that some practices of tawarruq in Malaysia did not comply with the Shari'ah, mainly due to improper sequencing of contracts and absence of commodity. The research suggested that the key SNC event determinants in tawarruq financing were lack of understanding and knowledge, inadequate control mechanism and reporting, ineffective functional structure, incompatibility of system to the execution of Islamic products, improper document execution and sequence, and inadequate internal policies and governing rules. Finally, the research proposes a Sharī'ah methodology and mitigation mechanism for IBs to deal with SNC events in the practice of tawarruq financing in Malaysia. The findings of the research are expected to serve as a reference source to industry players and regulators in formulating an appropriate policy and framework to enhance Sharī'ah governance and compliance practices in IBs in Malaysia.